Democracy : problems and perspectives - Axtmann, Roland (Edinburgh University Press, 2007)
Democracy: Problems and Perspectives provides a critical review of the scholarly and political debates about democratic thought and of arguments about democratic practice. On the basis of an interpretation of Immanuel Kant's political philosophy, the book presents democracy as a regime type in which citizens, who are united to give law, rule themselves and where such self-rule is exercised by citizens who embrace local and global patriotism. In the course of developing this idea of democracy, the book addresses issues such as human rights and their relationship to democracy; the policy of the global promotion of human rights and democracy; sovereignty and the nation-state; popular sovereignty and multicultural citizenship; and cosmopolitanism and cosmopolitan democracy. The book will stimulate controversial discussions about the varieties of democratic imaginations and visions, past and present as well as the future of democracy in the current stage of globalisation. Key Features Presents a broad range of thinkers, theoretical and political positions and arguments Clearly links theory and practice Uses case studies to elucidate the theories discussed Covers a broad range of theories of democracy